Acoustic energy generators - I. A. Semin; M. G. Kuznetsov; V. V. Kosulina (Известия высших учебных заведений: Проблемы энергетики)
The possibilities of the use of acoustic energy generators in various industries. We describe the structure and operation of a piston compressor acoustic gas. The generalized formula for the case of absence of radiation and the pipe with a sharp edge at the free end, which allows to establish a connection between the pressure and velocity of the gas in the plenum at the fundamental harmonic